Demokrasi tanpa Demos: Problem Gerakan Occupy dalam Era Informasi - Falahi, Ziyad (UI Scholars Hub, 2014)
This article examines the future of Occupy, which has become a leaderless resistance movement with people of many colors, genders, and political beliefs that say together that the neoliberal system isn't working for us. Moreover, now the Zuccotti model is morphing, and Occupy is undergoing a period of sustained global innovation. However, several large demonstrations have taken place all over the world in recent years after global crisis in 2008. But, The ancient discussion about the purposes of wealth and the conflict between oligarchy - rule of the rich - and democracy - the rule of the demos/the people comes to the fore once again within the current systemic crisis, The problems appear when Occupy use the development of information and social media to call for social, economic justice because the advance of Informations era led dramatical reduction of reality, which often called by